If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -13 = 30 Reorder the terms: -13 + 6x = 30 Solving -13 + 6x = 30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 6x = 30 + 13 Combine like terms: -13 + 13 = 0 0 + 6x = 30 + 13 6x = 30 + 13 Combine like terms: 30 + 13 = 43 6x = 43 Divide each side by '6'. x = 7.166666667 Simplifying x = 7.166666667
| abs((3x-7)/19)-14=0 | | 1/2=91/4 | | -3y^2-9y=1 | | 2n+7=5 | | 3(n-6)=-28+n | | 10z+3=7 | | 3n(n-6)=-28+n | | 4x-3(2x+4)=0 | | 4x-5=6x+4 | | x-16=41 | | 4x+188=6x+132 | | -20+7k=8k | | 7(2n-4)=(8n+1)+1 | | -2/3*Y+8=26 | | 3g+3=15 | | x+(-3)=-0.6 | | 8(x+6)=148 | | -8(-2+4n)=-38-5n | | 10-17f=-4-10f | | 6/(n^2-7n+12)=0 | | 7n+5=7 | | -3x+3=17 | | 4x+120=x(8+6) | | x=(-5*2)+(2*4) | | 12=x/2+20 | | -y^2+2y=-8 | | 284.2x+147.6y+51.7z=483.5 | | 3n+14=3 | | 5x=2x-42-3x | | y+3=17/11(x+5) | | 0=6x-14 | | 6(3n-3)=(9n+3)+8 |